Competitive strategies of internationalization, searching and creating markets - O. V. Mickhailov (Управление)
Actuality, content and advantages of strategies of the business internationalization, detecting and creating new markets are often remaining underestimating and ignoring of many subjects of the world economy. During formation of strategies and competitive advantages are missed the problems and possibilities of the world market and competition for the accelerated and outstriped self-developing of the business subjects. The gap is increased between traditional approaches to the strategies and real needs of the world, between temporary advantages and stable competitiveness, between competitive leaders and majority subjects of the world and national economies. The existing barriers for business internationalization are determined mainly by the traditional mental-goal oriented arrangements. Considering strategies are connected with ensure of the leadership on the world markets, that means more than the largest market share or quantitative its changes.The modern leadership in the world includes the superiority in innovation ability unique technologies, key competencies, setting up perspective directions of progress, new standards and game rules for the competitors. The psychological leadership often precedes the market leadership, it is its cause and foundation. The world market champions are highlighted by psychology superiority and intellectual leadership, implying desire to appoint the tendencies on the market not only go after them. The hidden champions became leaders, because they offered entire world their best and incessant improved products/services to all world clients. The combination of specialization (concerning products and know-how) and global broadening of the market/niche has diversity advantages, including of economies on scale, experience curve and temporal monopolization of the market niche.The strategy of revealing and creating new markets and market niches can form and create not only big companies, but middle and small enterprises, having unusually initiatives, invention initiatives, creation capabilities in finding and creating the new markets/niches. Transnational expanding the business can be calling out by the different motives, but it should start as early as possible and realise as quickly as possible. The leaders of the world economy create their products, possibly more distinctive and not accept еру definition and the boundaries of the market, given by their competitors, instead, they determine their market themselves.